UMP inks MoU with Turkey’s Duzce University to promote tertiary education, research and bilateral relations - UMP, PNC (2019)
Universiti Malaysia Pahang (UMP) recently inked a Memorandum of Understanding (MoU) with Duzce University (DU) of Turkey to boost developments in academic and research, as well as to strengthen bilateral relations between the two nations and public institutions of higher learning.